Understanding the Charge Storage Mechanism to Achieve High Capacity and Fast Ion Storage in Sodium‐Ion Capacitor Anodes by Using Electrospun Nitrogen‐Doped Carbon Fibers. (26th April 2019) - Yan, Runyu; Josef, Elinor; Huang, Haijian; Leus, Karen; Niederberger, Markus; Hofmann, Jan P.; Walczak, Ralf; Antonietti, Markus; Oschatz, Martin
Abstract: Microporous nitrogen‐rich carbon fibers (HAT‐CNFs) are produced by electrospinning a mixture of hexaazatriphenylene‐hexacarbonitrile (HAT‐CN) and polyvinylpyrrolidone and subsequent thermal condensation. Bonding motives, electronic structure, content of nitrogen heteroatoms, porosity, and degree of carbon stacking can be controlled by the condensation temperature due to the use of the HAT‐CN with predefined nitrogen binding motives. The HAT‐CNFs show remarkable reversible capacities (395 mAh g −1 at 0.1 A g −1 ) and rate capabilities (106 mAh g −1 at 10 A g −1 ) as an anode material for sodium storage, resulting from the abundant heteroatoms, enhanced electrical conductivity, and rapid charge carrier transport in the nanoporous structure of the 1D fibers. HAT‐CNFs also serve as a series of model compounds for the investigation of the contribution of sodium storage by intercalation and reversible binding on nitrogen sites at different rates. There is an increasing contribution of intercalation to the charge storage with increasing condensation temperature which becomes less active at high rates. A hybrid sodium‐ion capacitor full cell combining HAT‐CNF as the anode and salt‐templated porous carbon as the cathode provides remarkable performance in the voltage range of 0.5–4.0 V (95 Wh kg −1 at 0.19 kW kg −1 and 18 Wh kg −1 at 13 kW kg −1 ). Abstract : Carbon nanofibers with high nitrogen content are synthesized by electrospinning of a nitrogen‐rich precursor and subsequent condensation. Resulting nanofibres show remarkable performance as an anode material for sodium storage. The sodium storage mechanism is systematically investigated. It indicates the intercalation and reversible binding of the metal on nitrogen sites at different potential ranges and different rates.